2003
DOI: 10.1128/ec.2.6.1246-1252.2003
|View full text |Cite
|
Sign up to set email alerts
|

pH Response Transcription Factor PacC Controls Salt Stress Tolerance and Expression of the P-Type Na + -ATPase Ena1 in Fusarium oxysporum

Abstract: Fungi possess efficient mechanisms of pH and ion homeostasis, allowing them to grow over a wide range of environmental conditions. In this study, we addressed the role of the pH response transcription factor PacC in salt tolerance of the vascular wilt pathogen Fusarium oxysporum. Loss-of-function pacC ؉/؊ mutants showed increased sensitivity to Li ؉ and Na ؉ and accumulated higher levels of these cations than the wild type. In contrast, strains expressing a dominant activating pacC c allele were more salt tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
57
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 23 publications
7
57
0
1
Order By: Relevance
“…This pathway, named Pal/Rim, involves the action of different proteins that convey the pH stimulus to a key zinc finger transcription factor, PacC (Rim101), which activates transcription of genes induced at alkaline pH and represses genes induced at acid pH (8,15,26,44). Further studies proved the wide distribution of similar (although not identical) pathways in other ascomycetes and deuteromycetes (9,13,25,34,43). These studies have demonstrated that the function of PacC/Rim101 is more complex than simply regulating the transcription of pH-dependent specific enzymes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This pathway, named Pal/Rim, involves the action of different proteins that convey the pH stimulus to a key zinc finger transcription factor, PacC (Rim101), which activates transcription of genes induced at alkaline pH and represses genes induced at acid pH (8,15,26,44). Further studies proved the wide distribution of similar (although not identical) pathways in other ascomycetes and deuteromycetes (9,13,25,34,43). These studies have demonstrated that the function of PacC/Rim101 is more complex than simply regulating the transcription of pH-dependent specific enzymes.…”
mentioning
confidence: 99%
“…These studies have demonstrated that the function of PacC/Rim101 is more complex than simply regulating the transcription of pH-dependent specific enzymes. Additional processes in which PacC/Rim101 plays a regulatory role include meiosis, morphogenesis, and salt stress tolerance (9,23,36,43; reviewed in references 32 and 33).…”
mentioning
confidence: 99%
“…It is required for the hyphal formation at alkaline pH in C. albicans, in particular by repressing NRG1 expression in a pHdependent way (El Barkani et al, 2000;Lotz et al, 2004). Moreover, the resistance of cells to high levels of Ca 2+ and Li + requires activity of the Rim pathway, and the subset of ESCRT components needed for Rim101p processing in S. cerevisiae (Lamb & Mitchell, 2003;Platara et al, 2006), in C. albicans (Kullas et al, 2007) and in Fusarium oxysporum (Caracuel et al, 2003). In addition, the Rim pathway participates directly in cell-wall assembly, and acts in parallel with the protein kinase C (PKC) pathway in S. cerevisiae (Castrejon et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is also upregulated in response to alkaline conditions (Tilburn et al, 1995). In addition, PacC in some filamentous fungi was found to be involved in salt resistance (Caracuel et al, 2003). BbPacC was induced by both alkaline conditions and salt stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1b). In Fusarium oxysporum, PacC was found to be necessary for salt resistance (Caracuel et al, 2003). This prompted us to investigate the response of BbPacC to salt stress, and the results show that in addition to an alkaline pH, BbPacC was also induced by salt stress (Fig.…”
Section: Bbpacc Is Highly Induced By Alkaline Ph and Salt Stressmentioning
confidence: 99%